pemikiran PEMIKIRAN CHRISTIAN SNOUCK HURGRONJE DAN IMPLIKASINYA PADA UMAT ISLAM DI INDONESIA (PENDEKATAN TAFSIR AL-QUR’AN): Pemikiran Christian Snouck Hurgronje - Mustaqimah, Mustaqimah (Farabi, 2024)
This study has a focal point to find out the thoughts of Christian Snouck Hurgronje and its implications for Muslims. The research method used is library research using the Qur'anic and historical interpretation approaches. The data sources used are primary data sources, namely literature related to Snouck Hurgronje's thoughts in the form of books, articles and others. While secondary data sources are obtained from Tafsir Al Quran. The results showed that Snouck's thoughts about Islam include social society, colonial politics and the spread of European culture. This has implications for the retreat of Muslims in the political realm and considers it not part of Islam (separation between religion and politics / secularization) and has an impact on limiting the influence of Islamic law, in this case the interpretation of QS. Al-Baqarah 120 reminds Muslims to be careful with thoughts the notion of secularization.